(3eWGdY GdCfXGQ aj TQM WhGdY GdCfhGQs - (3CHh GdKfGA TeS GdOjf eMehO Hf YHO GdQMef GdCUagGfjs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO def hLhH hLhOg hHYO aEf CYXe GdYdhe ehVhYkG hCbhGgG CUhdkG haQhYkG gh Yde CUhd GdOjf djchf HGYK ddeMUdjf Ydi WdHg s
(3BNQgG (B:s
(3GdeHMK GdNGeS ai aVd GdUMGHI jLH JYXje LejY CUMGH GdfHi Udi Gddg Ydjg hSde GdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGHs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
Keywords: (3CUhd Gdabgs